THE PROBLEM OF THE BASIC UNIT OF TEXT - Aghayeva , Zuleikha (Collection of scientific papers «ΛΌГOΣ», 2022)
The problem of the sign unit underlying the formation of an expanded text primarily affects the definition of the textual status of the sentence. After all, it is the sentence that is recognized as a grammatically formed integral unit of speech according to the laws of this language – the main means of forming, expressing and communicating thoughts. Already in this almost universally accepted approach to a sentence, its verbal or textual connectedness is clearly indicated. The textual connectedness of the sentence did not go unnoticed by syntaxists of the last generation. In fact, without taking into account this side of the sentence, it would be impossible to read its meaning in the context of speech. Accordingly, the text was quite naturally taken by linguists-syntaxists of past times as a background for revealing the inner structure of the sentence. At the same time, the sentence seemed to be the highest grammatically organized segment of the language.